Chapter Metodologia, tecniche e strumenti della ricerca La qualità dei Corsi di studio LM 50 e LM 57&85. La prospettiva degli studenti dell'Università di Firenze - mancarella, dino (Studies on Adult Learning and Education, 2022)
The quality of higher education curricula has received increasing attention in recent years. The Sustainable Development Goals 2030 emphasise the role of quality education for developing employability skills and for achieving decent jobs. The Bologna Process understands the quality of study courses as their capacity to develop employability for its graduates. In this study, we present the methodology, the techniques and the instruments of the research focussed on the quality of LM 50 and LM 57/85 study courses from the perspective of students enrolled in the University of Florence.